2009
DOI: 10.2165/00019053-200927030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Varenicline, an Oral Smoking-Cessation Drug, in Japan

Abstract: As with any data of this nature, there is some uncertainty in the results and further research is warranted. However, based on the results of this pharmacoeconomic evaluation, varenicline, the first non-nicotine, oral treatment developed for smoking cessation, appears to be cost effective and may contribute to future medical cost savings in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…Several such treatments, bupropion and varenicline, are more costly than NRT and appear to display greater risks [30][31][32] . A logical, stepped-care approach would thus entail initial use of pre-cessation NRT, assignment of nicotine dose based on dependence level and quit-success genotype scores, identification of individuals who do not reduce CO sufficiently and prompt 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several such treatments, bupropion and varenicline, are more costly than NRT and appear to display greater risks [30][31][32] . A logical, stepped-care approach would thus entail initial use of pre-cessation NRT, assignment of nicotine dose based on dependence level and quit-success genotype scores, identification of individuals who do not reduce CO sufficiently and prompt 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[29] In a Japanese study using an alternative Markov model and conducted from a healthcare payer perspective, 12 weeks' therapy with varenicline dominated counselling alone, with regard to the incremental cost per QALY gained. [37] Additional BENESCO analyses (conducted in Sweden, [35] the US [36] and Scotland [24] ) estimated that when only direct costs were considered, an additional 12 weeks of varenicline therapy was associated with acceptable incremental costs per QALY gained versus varenicline for 12 weeks alone, [24,35,36] and dominated bupropion SR, [36] nicotine replacement therapy [36] or unaided cessation, [36] with regard to the cost per QALY gained. The cost effectiveness of an additional 12 weeks of varenicline therapy, versus 12 weeks alone, was maintained when indirect costs were also considered.…”
Section: Pharmacoeconomic Analyses Of Vareniclinementioning
confidence: 99%
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%